Mobility of Multibody Systems in Terms of their Incorrectness - Sapietova, Alzbeta; Saga, Milan; Shimanovsky, Alexandr; Sapieta, Milan (Communications - Scientific letters of the University of Zilina, 2014)
The paper presents examples of incorrectness from the point of view of body and Multibody System (MBS) kinematics. This incorrectness should be kept in mind when modeling Virtual Prototypes (VP) of MBS. During the analysis or synthesis of MBS it is necessary to correctly determine the degree of freedom (DOF) of mechanisms in order to properly design the mechanism. The basic relation for the DOF computation does not include parameters such as special dimensions of links or their mutual configuration and geometric constraints. In many cases, these issues require individual approach, i.e. by analyzing the properties of incorrect MBS to identify the causes of their incorrectness and apply the computation method to the actual mobility. The paper contains samples to illustrate a particular topic.